SYNERGISTIC EFFECT OF DIRECT AND ALTERNATING ELECTRIC CURRENT TREATMENTS AND BRONOPOL TO INACTIVATE BACTERIA FOUND IN HIDE SOAK LIQUORS - (:unkn) unknown (AMER LEATHER CHEMISTS ASSOC, 2013)
It is well known that bacteria on hides and in the hide-soak liquors do damage that compromises leather quality. These harmful bacteria are resistant to the antibacterial agents used in the hide industry. In this research the synergistic effect of a combined electric current treatment using both 1.5 A direct and 2.0 A alternating electric currents, followed by 1 g/L of bronopol treatment on mixed culture of Gram positive and Gram negative hide bacteria was examined in a liquid medium containing 2% NaCl and organic substances. Enterobacter cloacae, Vibrio fluvialis, Pseudomonas luteola, Staphylococcus cohnii, Enterococcus faecium and Bacillus pumilus were used as test isolates. Six different experiments were carried out on the mixed culture of test bacteria to determine the efficiency of the synergistic effect of a combined electric current treatment. Bacterial cell counts were reduced to low level in a short period using the electric treatment. More than 2 log reduction factor of the mix culture was observed within 12 min after the electric current treatment, and the damaged bacteria were killed easily by bronopol in five hours. DC and AC electric currents in combination with antimicrobial agents may be used to more efficiently exterminate the bacteria found in the hide-soak liquors.
Keywords: TANNING PROCESSES; AEROBIC BACTERIA; CURED HIDES; EFFICACY; MICROBIOLOGY; ANTIBIOTICS; POPULATIONS; SALT